THE POLITICAL STRATEGY OF WINNING THE YOUTH MAHENDRAWAN-SUJIWO COUPLE IN THE ELECTION OF THE REGENT AND VICE REGENT OF KUBU RAYA 2018 - Nurdiana; Bakran; Erdi; Thamrin (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2022)
Kubu Raya Regency, which is one of the areas that participated in the contested regional elections in 2018. The defeat in the 2013 regional elections did not dampen the spirit of Muda Mahendrawan to continue his struggle in the 2018 Kubu Raya elections to win the regional elections with his deputy, Sujiwo. This study was conducted using a qualitative descriptive method to analyze the political strategy used by the Young Mahendrawan-Sujiwo couple to win the 2018 Kubu Raya Regent and Deputy Regent Election. The data were obtained from interviews and documentation studies. The results of the study found that there were two strategies used by the Young Mahendrawan-Sujiwo couple in winning the 2018 Regional Head Elections for the Regent and Deputy Regent of Kubu Raya, namely an offensive strategy and a defensive strategy. The offensive strategy or attack strategy is carried out by forming a team of volunteers so that they move militantly and carry out closed and open campaigns that socialize the vision, mission, and innovative work programs that are attractive to the community. The defensive strategy or defensive strategy is carried out by going to the field face to face to defend the people who have the potential to vote and maintain a positive image in stemming the negative campaigns that arise.